ANALISIS YURIDIS TERHADAP PRAKTEK PENJAMINAN HAK TANGGUNGAN YANG TIDAK DIDAFTARKAN OLEH KREDITUR PERORANGAN - Helen, Helen; Purba, Hasim; Sembiring, Rosnidar (BULETIN KONSTITUSI, 2023)
ABSTRACT Guarantee sellers in the form of land are accepted because land has high economic value and does not experience a decrease in value, so that the state regulates everything related to land as outlined in the Basic Agrarian Law which provides for arrangements for land use and supervision. Land guarantee institutions that provide strong legal certainty and protect both creditors and debtors, namely Mortgage Rights. The problem in this study is regarding the legal rules governing the obligation to register mortgage guarantees, the position of mortgage guarantees that are not registered by individual creditors, and legal protection for the parties in guaranteeing mortgage rights that are not registered by individual creditors. Normative juridical research method The type of data used is secondary data consisting of primary, secondary and tertiary legal materials. The technique of collecting data is by studying the literature. The data that has been obtained is then analyzed qualitatively to obtain descriptive research results. This research shows that lending and borrowing money usually uses the submission of property rights certificates as collateral, the use of collateral in the form of land certificates must be based on mortgage rights as collateral for repayment of debts to creditors based on the UUPA. From the copy of the mortgage land book and the copy of the Mortgage Deed, the APHT must be registered at the local land office, but in practice the registration of the mortgage is negligent or the creditor does not register it, giving rise to legal consequences.